Neurodiversity and (Semantic) Space for the Academic Inclusion of People on the Autism Spectrum - Ryszarda Cierzniewska; Dorota Podgórska-Jachnik (Ignatianum University Press, 2021)
There is a need to rethink functioning and the role of universities that implement inclusive education, understood as high-quality education for everybody, available at all levels of education  because of the increasing number of neurodiverse people (with ADHD, autism, dyslexia and other disorders classified as neurodevelopmental).. The aim of our hermeneutical work is an attempt to identify opportunities and limitations on an empirical and theoretical level for creating conditions for the inclusion of students defined as neurodiversity. The research material consists of published own and other authors' studies, and the direction of exploration is determined by the following questions: Are there theoretical and empirical premises for the claim of full inclusion in the academic education of neurodiverse students? What are the research-related limitations that constitute a barrier to the academic inclusion of neurodifferent adolescents? The theoretical background of our work is the theories of social constructivism as defined by Alfred Schűtz, Peter Berger and Thomas Luckmann. The research revealed theoretical and empirical premises confirming the validity of the claim regarding the inclusion of neurodiverse students in academic education due to the intellectual potential of young people, their high self-awareness and the need to provide a growing number of neurodiverse students with conditions for maturing to self-determination in adult life. In Poland, but also in other European countries, the number of students diagnosed with an autism spectrum is not monitored at the national level. Single studies conducted in Poland indicate the similarity of the problems of this group of students with the results of explorations carried out in other countries, and include dropout during the first year of studies, difficulties in relationships with peers, a feeling of loneliness, and a low level of employment after graduation. A large number of people with autism spectrum does not study at all. One of the barriers may be the availability of higher education, which is related to the cultural and economic status. This aspect has not been taken into account in Polish and international research. There was also little dissemination of the idea of neurodiversity, which may be important for the perception of students with the autism spectrum.